2010
DOI: 10.1002/clc.20777
|View full text |Cite
|
Sign up to set email alerts
|

Possible Participation of Endothelial Cell Apoptosis of Coronary Microvessels in the Genesis of Takotsubo Cardiomyopathy

Abstract: Background: Takotsubo cardiomyopathy (TCM) is characterized by systolic ballooning of the left ventricular apex. It is triggered by emotional or physical stress, but the exact mechanism through which stress leads to TCM is not known. Hypothesis: Coronary microvessel apoptosis is the missing link between stress and TCM. Methods: In 8 female patients with TCM, plasma catecholamines,Thrombolysis in Myocardial Infarction (TIMI) coronary flow grade and myocardial perfusion grade, and apoptosis of the coronary micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…Irrespective of the ballooning variant, this abnormality in flow is frequently observed in all three epicardial vessels, suggesting a downstream microcirculatory disturbance that may be sympathetically mediated. This idea is supported by a study from Japan in which patients with SCM were found to have elevated plasma catecholamine levels and evidence from left ventricular endomyocardial biopsy of microvascular endothelial cell apoptosis (Uchida et al 2010).…”
Section: Possible Pathophysiologic Mechanisms Of Sympathetically Medimentioning
confidence: 95%
“…Irrespective of the ballooning variant, this abnormality in flow is frequently observed in all three epicardial vessels, suggesting a downstream microcirculatory disturbance that may be sympathetically mediated. This idea is supported by a study from Japan in which patients with SCM were found to have elevated plasma catecholamine levels and evidence from left ventricular endomyocardial biopsy of microvascular endothelial cell apoptosis (Uchida et al 2010).…”
Section: Possible Pathophysiologic Mechanisms Of Sympathetically Medimentioning
confidence: 95%
“…Administration of catecholamines, such as epinephrine and dobutamine triggers TTC 44 6. Extensive LV microvascular endothelial cell apoptosis observed in myocardial biopsy 45 7. Increased sympathetic tone from mental stress can cause vasoconstriction in patients without coronary artery disease 46 8.…”
Section: Catecholamine-induced LV Dysfunction and Microvascular Dysfumentioning
confidence: 95%
“…The plasma concentrations of catecholamines during the acute phase were 2-3-times higher than in patients with AMI and heart failure, and 20-times higher than in normal adults (Wittstein et al, 2005). Uchida et al also observed elevated levels of plasma epinephrine and norepinephrine in patients with stress-induced cardiomyopathy (Uchida et al, 2010). The plasma half-life of epinephrine is only 3 min (Zeb et al, 2011, as cited in Ferreira & Vane, 1967, so measurement of catecholamines should be conducted at the time of symptom onset.…”
Section: Laboratory Findingsmentioning
confidence: 95%
“…As mentioned above, contrast echocardiographic perfusion imaging, CMR and nuclear imaging provide evidences of coronary microvascular dysfunction. Uchida et al investigated the hypothesis that coronary microvessel apoptosis could be the missing link between stress and stress induced cardiomyopathy (Uchida et al, 2010). Plasma catecholamines, thrombolysis in myocardial infarction (TIMI) coronary flow grade and myocardial perfusion grade, and apoptosis of coronary microvessels in the biopsied myocardial specimens by terminal deoxynucleotidyl transferase-mediated nick end-labeling (TUNEL) were examined in 8 female patients with stress-induced cardiomyopathy.…”
Section: Catecholamine and Microvascular Spasmmentioning
confidence: 99%
See 1 more Smart Citation